The Effect Of Cyberloafing On The Work Productivity Of Muhammadiyah Parepare University Employees - Syah, Firman; Sudirman, Sudirman (Economos : Jurnal Ekonomi dan Bisnis, 2024)
Cyberloafing is an important issue that develops along with the development of internet use in an organization. This study aims to determine whether Cyberloafing has a significant effect on employee work productivity at the University of Muhammadiyah Parepare using quantitative descriptive methods. The population in this study is 358 people consisting of 248 lecturers and 110 educators, data sourced from the 2023 database of the ministry of education and culture and the General Bureau of the University of Muhammadiyah Parepare. Sampling was carried out randomly as many as 78 people. Data collection techniques in this study through observation and using questionnaire instruments. Questionnaires are used when researchers want to know the perceptions or habits of a population based on respondents. The analysis technique used is Simple Linear Regression with SPSS. The results showed that Cyberlofing did not have a significant effect on the work productivity of Muhammadiyah Parepare University Employees, and Cyberloafing activities by Muhammadiyah Parepare University Employees were negative, so that Work Productivity could be said to be good.